Small Steps, Big Security: TAM-Powered Insights of Cybersecurity Adoption Among Small-And-Medium Entrepreneurs in Digital Business - Radzi, Nur Raidah; Tajuddin, Siti Nor Amalina Ahmad; Bahari, Khairul Azam (Journal of Ecohumanism, 2024)
Embracing digital business enhances company resilience, yet small and medium-sized enterprises (SMEs) often lack resources to combat cyber threats, unlike larger enterprises. Sophisticated cyberattacks surpass standard antivirus software, necessitating a shift in cybersecurity strategies. Therefore, this study aimed to investigate the relationship between knowledge, perceived usefulness, perceived ease of use, and the adoption of cybersecurity among small-and-medium entrepreneurs in Perak, Malaysia. Guided by the Technology Acceptance Model (TAM), this ongoing research employed a quantitative approach by distributing questionnaires to 400 digital entrepreneurs in the small and medium-sized business sectors in Perak. The findings revealed that the majority of entrepreneurs possessed a relatively high level of knowledge about cybersecurity. Furthermore, the study identified a strong positive correlation between knowledge and perceived usefulness (correlation coefficient r = 0.639), as well as a moderately positive correlation between knowledge and perceived ease of use (correlation coefficient r = 0.435) among small and medium entrepreneurs in Perak. Consequently, this study contributes to a better understanding of the Technology Acceptance Model (TAM) within the context of perceived usefulness, perceived ease of use, and the adoption of cybersecurity, thereby enriching the existing literature on cybersecurity among small and medium entrepreneurs in the era of digital business.